A study on clinical profile, liver dysfunction and outcome of dengue infection in children - Neniwal, Vishal Kumar; Chohan, Pooja; Kumar, Pankaj; Neniwal, Nitin (International Journal of Contemporary Pediatrics, 2026)
Background: Dengue viral illness is a matter of serious concern in all world, specifically because of absence of specific antiviral medicine and vaccine. Severe dengue has a mortality of 2-5%, but when left untreated the mortality rate is high as 20%, and liver involvement tends to be more severe infection in children. Methods: This is a prospective observational study conduct in our Department from July 2020 to December 2022. Total patients in our study were 90. The objective of our study was to determine the relationship between liver dysfunction, kinetics of liver function tests (LFTs) and severity of hepatitis on the outcome in pediatric dengue illness, with special attention to preserved life of patient because its life-threatening potential. Results: Dengue confirmed cases were divided into two group; severe dengue (SD) and non-severe dengue (NSD) group. Mean age was 7.2 years ± 3.74-year Age, 38.9% were females. All cases were suffering from fever, abdominal pain was present 51.1% in cases, Liver function tests SGOT (AST), SGPT (ALT) and ALP, bilirubin and albumin were deranged in both groups of children. Outcome of study 8 (25.8%) patients out of 31 were death from severe dengue group. Conclusions: Liver Function Tests (LFT) monitoring done during acute dengue illness was a predictor of mortality in children with Dengue illness. Higher level of derangement in Liver dysfunction in children with dengue illness associate with higher rate of mortality.